Biochemical study of striped catfish Pangasianodon hypophthalmus broodstock induced by PMSG hormone + anti‒dopamine and turmeric addition - Arfah, Harton; Sudrajat, Agus Oman; Suprayudi, Muhammad Agus; Junior, Muhammad Zairin (Indonesian Society of Scientific Aquaculture (ISSA), 2018)
ABSTRACT This study aimed to evaluate biochemical changes (cholesterol, triglyceride, HDL, LDL, glucose, and plasma protein) on striped catfish Pangasianodon hypophthalmus broodstock induced with PMSG hormone and turmeric addition. An observation was also done to blood glycogen content. The striped catfish broodstock was fed on commercial feed without any addition (control) and with turmeric addition (HKu). In control treatment, there was a decreasing on cholesterol, meanwhile, the triglyceride (TG) value was increased. The HDL concentration was decreased in 2nd sampling and increased in 4th sampling. In 1st until 4th sampling, glucose was quite stable, while LDL was on extremely low concentration. In HKu treatment, the cholesterol value was higher than the control treatment. The TG concentration also higher than control in 3rd sampling and decreased in 4th sampling. The HDL concentration was increased and higher than the control treatment, while LDL concentration was lower. The liver glycogen content on the control and HKu treatment were 0.015 (mg/100 mL) and 0.181 (mg/100 mL) respectively; while in the flesh of the control and HKu treatment were 0.76 (mg/100 mL) and 1.19 (mg/100 mL) respectively; and in the gonad of control and HKu treatment were 0.10 (mg/100 mL) and 0.70 (mg/100 mL) respectively. It was shown that the glycogen content in the liver, flesh, and gonad on experimental fish was higher than control treatment. Keywords : biochemistry, hormone, turmeric, channel catfish, reproduction ABSTRAK Penelitian ini bertujuan untuk mengkaji perubahan biokimia (kolesterol, trigliserida, HDL, LDL, glukosa dan protein plasma) induk ikan patin Pangasianodon hypophthalmus yang diberi perlakuan hormon PMSG dan kunyit (HKu). Pengamatan juga dilakukan terhadap glikogen dalam darah induk patin. Induk ikan patin diberi pakan tanpa penambahan kunyit (kontrol) dan pakan yang diberi HKu. Hasil penelitian pada kontrol menunjukkan adanya penurunan kolesterol, sedangkan pada TG mengalami peningkatan. HDL menurun pada sampling ke‒2 dan meningkat pada sampling ke‒4. Sementara itu, pada LDL rendah sekali dan pada glukosa terlihat stabil dari sampling ke‒1 sampai ke‒4. Pada perlakuan HKu terlihat bahwa pada kolesterol menghasilkan nilai lebih tinggi dibanding kontrol. Pada TG terlihat juga nilai lebih tinggi dibanding kontrol pada sampling ke‒3 dan menurun pada sampling ke‒4. Konsentrasi HDL meningkat dan lebih tinggi dibanding kontrol, sedangkan nilai LDL lebih rendah. Data yang diperoleh pada kadar glikogen hati perlakuan kontrol adalah 0,015 (mg/100 mL) dan HKu 0,181 (mg/100 mL); sedangkan pada daging kontrol sebesar 0,76 (mg/100 mL) dan HKu 1,19 (mg/100 mL); serta gonad kontrol 0,10 (mg/100 mL) dan HKu 0,70 (mg/100 mL). Hal ini menunjukkan kadar glikogen pada hati, daging, dan gonad ikan yang diberi perlakuan bernilai lebih tinggi dibanding kontrol. Kata kunci : biokimia, hormon, kunyit, ikan patin, reproduksi